Narasi Kepribadian Nabi Muhammad Saw sebagai Teladan pada Buku SKI Tingkat MI/SD - Nasution, Abdul Gani Jamora; Bilqish, Alifia; Munthe, Abdal Rizky; Lubis, Nabila Suhaila (Al-DYAS, 2023)
Prophet Muhammad SAW which for Muslims, he is a symbol of a good personality that Muslims should emulate wherever they are. Rasulullah SAW must be used as a role model and a good example for all his people, the figure of Prophet Muhammad SAW is a figure who has a good personality. The Prophet Muhammad SAW besides having an honest attitude (Arabic: Shiddiq), also has the characteristics of Amanah (Trustworthy),Tabligh (Conveying), and Fathonah (Smart).This research uses a qualitative approach with an analytical descriptive method. The analytical-descriptive method is an attempt to describe, analyze and explain the results of the research. The purpose of the analytical-descriptive research is to awaken the younger generation to cultivate honest behavior in words through Islamic cultural history education in elementary-age children at the MI/SD level. For this reason, data checking in this study was carried out using reference materials. The Prophet Muhammad SAW was a human figure who had great morals and noble character. The noble personality of the Prophet Muhammad SAW is of course a blessing for those who understand, emulate him, and live it in their daily lives.